The impact of audit quality in companies performance: a comparison between northern and southern Europe - Caldeira, Catarina da Cunha (2019)
Since the financial crisis, a variety of questions have been raise about Europe’s south and north division. The origin of this big gap between countries is very complex and involves financial, political and social outlooks. In order to answer this debate, the purpose of the present study is to investigate and understand if there is indeed a different audit quality in northern compared to southern European countries, basing the research in ninety listed companies from Finland, Norway, Denmark, Sweden, France, Belgium, Italy, Portugal and Spain. The objectives of this investigation consist on examining the effect of auditor size, auditor change, audit fees, auditor opinion and board size, as measures of audit quality and analyze to what extent the five measures can reveal different results between the two European regions. The conclusions show that board size is rejected and do not represent an explanatory variable for audit quality. Audit size, audit opinion and auditor change have a statistical significant relation with just one of the measures of financial performance and profitability, which present a limitation, because it only dependents on the choice of the precise indicator. Audit fees is the most significant variable to explain the audit measure of the research model. Reinforcing the importance of audit fees in order to explain audit quality. Furthermore, by comparing the north and south region, it is possible to conclude that audit fees and board size present different results depending on the region.